Metastasis within a metastasis to the thyroid: A rare phenomenon - Wong, Yin PIng; Ahmad Affandi, Khairunisa; Tan, Geok Chin; Muhammad, Rohaizak (Wolters Kluwer - Medknow, 2017)
Metastatic disease involving the thyroid gland is uncommon. Solitary thyroid metastases from various primary sites particularly kidney, lung, and breast had been previously described. To the best of our knowledge, metastases from two topographically separate primary malignancies to the thyroid have never been documented hitherto. This is the first reported case of cancer-to-cancer metastasis involving an invasive breast carcinoma metastasized within a metastatic renal cell carcinoma in the nonneoplastic thyroid in a 58-year-old woman. Distinguishing a secondary thyroid metastases from a primary thyroid malignancy is utmost crucial as treatment differs. The possibility of tumor metastases from two separated primaries should always be considered in a tumor exhibiting malignant cell populations with two distinctive histomorphological appearances. The role of immunohistochemistry stains in equivocal cases cannot be overemphasized.